Theatre personnel’s perception of operating room resource allocation (2009)
Operating rooms (OR) in hospitals represents big investments and must be utilized efficiently. Inaccurate scheduling of OR resources often results in delays of surgery or cancellations of procedures. These are costly to the patient, surgical team and hospital. Existing literatures in the OR management lack consensus on the method of evaluating management decisions from the perspectives of personnel or those affected by management decision-making processes. Eight key informant interviews were conducted. Also, 50 Operating Theatre Personnel (OTP) i.e. Surgeons, OR Nurses, Anaesthetists, and Executive Officers in the Nigeria's premier University Teaching Hospital were asked to complete a survey questionnaire concerning operating theatre resource allocation in the hospital. Five close ended and 10 open-ended questions were used. (For example, how are the decisions to allocate OR resources in this hospital made?) Thematic analysis and descriptive statistics were done. The theoretical framework, accountability for reasonableness was applied. Forty-eight percent of the participants were ignorant of the framework guiding OR resource allocation. 54% of the respondents admitted the current mechanism for publicizing management decisions on OR resource allocation is ineffective. Another 50% of the respondents knew little about the mode of appealing against unfavourable allocation decisions. Participants' open ended responses revealed that hospital executives and a few consultant surgeons control the allocation of OR resources, with, little recourse to OR personnel's concerns. If operating theatre stake holders are excluded in the planning, allocation and evaluation of OR resources, the efficiency required in surgical services would never be realized irrespective of the dexterity of the surgical team.